2017
DOI: 10.1111/pde.13215
|View full text |Cite
|
Sign up to set email alerts
|

Punch and Scoop Technique for Removing Pilomatricoma

Abstract: Pilomatricomas are benign calcifying neoplasms derived from follicle matrix cells. Standard treatment for pilomatricomas involves complete surgical excision, with an overall low rate of recurrence. We discuss a simple alternative surgical technique that allows for removal of the lesion with less residual defect than complete excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Maranda et al . 's technique of punch and scoop of the lesion, although an improvement from the traditional wide local excision approach, still leaves a notable scar 8 . We decided to trial the Morals and McGoey's technique of I&C as it reported no recurrence with a median follow‐up period of 5 years 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maranda et al . 's technique of punch and scoop of the lesion, although an improvement from the traditional wide local excision approach, still leaves a notable scar 8 . We decided to trial the Morals and McGoey's technique of I&C as it reported no recurrence with a median follow‐up period of 5 years 7 .…”
Section: Discussionmentioning
confidence: 99%
“…A 4‐mm punch biopsy of the lesions would be taken, and through this defect the lesion would be curetted out. Following this, the defect would be filled with 25% trichloroacetic acid and left to heal by secondary intention 8 …”
Section: Introductionmentioning
confidence: 99%